Plate tectonics, cold adaptation and long-distance range expansion to remote archipelagos and the high Andes as drivers of a circumantarctic freshwater arthropod radiation - Villastrigo, Adrián; Lam, Athena; Van Dam, Matthew H; Scheunert, Agnes; Hájek, Jiří; Hendrich, Lars; Michat, Mariano C; Megna, Yoandri; Figueroa, Luis; Zenteno, Nilver; Ledezma, Julieta; Guerra-Serrudo, Fernando; et al. (Molecular phylogenetics and evolution, 2025)
Disjunct distributions, characterised by spatially separated populations of related species, offer insights into historical biogeographic patterns and evolutionary processes. This study investigates the evolutionary history of the diving beetle subfamily Lancetinae through a phylogenomic approach incorporating ultraconserved elements (UCEs) and heritage genetic markers. Our findings support an early Miocene origin for Lancetinae, with subsequent diversification influenced by historical vicariance events and long-distance dispersal. The divergence from the closely related subfamily Coptotominae in the late Cretaceous is not consistent with a Gondwanan origin, although highlights a likely Pangean origin for these taxa. This research underscores the significant impact of Gondwanan fragmentation on biogeographic patterns and highlights the remarkable dispersal capabilities of Lancetinae beetles.
Keywords: Animals; biologická evoluce; Phylogeography; Coleoptera; Genetic Speciation; DNA, Mitochondrial; modely genetické; Dispersal; brouci; Bayesova věta; Bayes Theorem; fyziologická adaptace; Evolution, Molecular; molekulární evoluce; Cold Temperature; Fresh Water; Phylogeny; Models, Genetic; Lancetes; sladká voda; Diving beetles; fylogeografie; mitochondriální DNA; Biogeography; Adaptation, Physiological; Sequence Analysis, DNA; vznik druhů (genetika); zvířata; sekvenční analýza DNA; Biological Evolution; nízká teplota; fylogeneze; Adaptation